CARA MENGAMBIL KEPUTUSAN YANG TEPAT UNTUK MEMILIH JURUSAN DAN PERGURUAN TINGGI YANG TEPAT PADA SISWA SMA DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Wilujeng, Fuji Rahayu (Universitas Bunda Mulia, 2018)
ABSTRACTAt this time, often encountered many students who feel wrong in choosing majors and the university even when they are already enrolled, it majors selected not according to their talents and interests. Early education of students and students will minimize the potential that they will feel disappointed with their choice when they are educated in college. Therefore, through community service activities is intended to provide education about how and step in selecting or determining the most appropriate option to continue their studies to pursue higher education. After this workshop, students feel very satisfied because they have an alternative keputuan in the selection of majors to continue to pursue higher education in accordance with their interests and talents. Keywords: Analytical Hierarchy Process, making decisions